Analisis Pengaruh Self Assessment dan Tax Amnesty Terhadap Kepatuhan Wajib Pajak - Elia Rossa; Lissa Rahmawati; Muh Farhan Yudamahendra; Muhammad Rivki Adrian; Nabila Syifaa Azzahra Suwandi; Neyla Safitri; Vina Hariyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Tax compliance is an attitude when taxpayers are able to fulfill their tax obligations with their own awareness. The change in the tax system which originally implemented an official assessment, changed to a self-assessment, is hoped that taxpayers will be more compliant in fulfilling their tax obligations, because taxpayer compliance and awareness greatly influences state revenues from the tax sector. The government also has another way to increase taxpayer compliance, namely by implementing tax amnesty. For taxpayers who take part in the Tax Amnesty program, they can receive forgiveness for the taxes they should pay as well as the elimination of administrative and criminal sanctions. Almost every country has an infrastructure development program to meet the welfare of the general public, including Indonesia and to run this program the main funds come from taxes. So taxes and values ​​have a very important and influential role in the country's development process and as financing for government expenditure for its implementation. This research aims: 1) to find out whether self-assessment has an effect on taxpayer compliance. 2) to find out whether the tax amnesty has an effect on taxpayer compliance. The writing in this article uses a qualitative method with a descriptive approach. So the research results show that self-assessment and tax amnesty have a positive effect on taxpayer compliance.